A study of recordkeeping practices of the administrative and academic offices of the New Era University - Mallari, Rogelio E.; Santos, Herminia H.; Aquino, Aurora (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
This study proposes the founding of a records management program for New Era University administrative and academic offices and the establishment of a University Records Center. These proposals have the ultimate goal of creating a University archive in the future. The initial task was to determine the current recordkeeping practices in the University. It proceeds to: a) remedy current recordkeeping problems in the University and avoid future ones, b) to support the current operations of the University offices through an effective records management program, and c) to ensure the classification, maintenance, retention, protection, and preservation of all University records. The survey method was used with the questionnaire as the basic instrument. The questionnaire carried three major headings as follows: historical background; recordkeeping practices; and the records retention and disposition. The major findings inferred the following conclusions: defective recordkeeping practices, untrained recordkeeping personnel, inadequate records security measures, limited storage area, unawareness of the importance of records inventory, and absence of guidelines in records retention and disposition. Suggestions and recommendations to improve the records handling of the University include the founding of a records management program, a records management directive, creating management advisory committee, employing competent records personnel, building a University Records Center, and creation of a records management manual.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: New Era University; Records management